PENERAPAN ALGORITMA FISHER YATES PADA GAMES EDUKASI PENGENALAN HEWAN BERBASIS MOBILE - Krisdiawan, Rio Andriyat (NUANSA INFORMATIKA, 2018)
Technological developments are growing today is very useful, especially in the use of mobile devices. One of the utilization of this mobile technology especially for children more use in game or game. With the rapidly growing game development, many games are more focused on entertainment and entertainment alone. There are still few games that provide education that is useful for the development of childrens education. In this case the author took the initiative to create an educational game that is able to provide benefits and provide an educational value. In the design of game puzzles, a randomization algorithm is required that can give good results in the randomization. The algorithm used in this research is yates algorithm. That is an algorithm that uses random, which can be implemented by a fisherman algorithm capable of providing biased results (results of randomization by fishermen that are difficult to predict the pattern of the results). This game development using RUP (Rational Unified Process) system development method. With system design based on UML object (Unified Modeling Language) and programming language to be used is programming language based on mobile android.Keywords: Games, Algorithms, Fisher Yates, Mobile Android, Puzzle Games, Educational Games